2021
DOI: 10.1039/d0gc04029k
|View full text |Cite
|
Sign up to set email alerts
|

One-pot self-assembly synthesis of Ni-doped ordered mesoporous carbon for quantitative hydrogenation of furfural to furfuryl alcohol

Abstract: Ni-doped ordered mesoporous carbons (Ni@OMC) were prepared by one-pot solvent evaporation-induced self-assembly (EISA) process with sustainable biomass-derived gallic acid as carbon precursor, F127 as soft template and Ni2+ as cross-linker...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…From this point of view, catalysts and experimental conditions are the main factors which impose a crucial influence on the selectivity in the reductive conversion of furfural [4,5] . Supported noble metal (Pt, Pd, Ru and Ir) as well as transition metal (Cu, Fe, Ni) nanoparticles have been proposed as heterogeneous catalysts for the direct hydrogenation (under H 2 pressure) and the catalytic transfer hydrogenation (using an organic molecule as the hydrogen source) of furfural [6–26] . Depending on the metal nature and structure (distribution of exposed active sites, such as edges, corners, terraces), furfural can adopt different adsorption modes on the active surface, [27] which are schematically depicted in Scheme 1 b.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, catalysts and experimental conditions are the main factors which impose a crucial influence on the selectivity in the reductive conversion of furfural [4,5] . Supported noble metal (Pt, Pd, Ru and Ir) as well as transition metal (Cu, Fe, Ni) nanoparticles have been proposed as heterogeneous catalysts for the direct hydrogenation (under H 2 pressure) and the catalytic transfer hydrogenation (using an organic molecule as the hydrogen source) of furfural [6–26] . Depending on the metal nature and structure (distribution of exposed active sites, such as edges, corners, terraces), furfural can adopt different adsorption modes on the active surface, [27] which are schematically depicted in Scheme 1 b.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the design of an effective catalytic system for the conversion of furan derivatives was one of the key problems for biomass conversion. It was reported that the furfural and HMF could be converted to a various of chemicals such as tetrahydrofurfuryl alcohol, [21–23] furfuryl alcohol, [24] furan‐2,5‐dicarbaldehyde, [25] furan‐2,5‐dicarboxylic acid, [26–30] 2,5‐dimethylfuran, [31–34] 1‐hydroxyhexane‐2,5‐dione (HHD), [35–48] cyclopentanone [49–54] and diols derivatives [55–59] . The products covered the areas of aldehydes, ketones, acids, esters, ethers, and diols.…”
Section: Introductionmentioning
confidence: 99%
“…In all the above cases, OMCs were efficiently applied as supercapacitors for energy storage. In addition, the applicability of OMCs can further be enhanced by loading active metals such as nickel and zinc on their surface [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Common doping methods include wet impregnation and coprecipitation, but both require complex operation procedure and may result in metal leaching [ 20 ].…”
Section: Introductionmentioning
confidence: 99%